THE IMPORTANCE OF EARLY TREATMENT OF CONGENITAL VISUAL DISORDERS IN CHILDREN AND THE CONSEQUENCES OF UNTREATED CONDITIONS (Universal International Scientific Journal, 2026)
This article is dedicated to highlighting the importance of early detection and timelytreatment of congenital visual disorders in children, as well as explaining, on a scientific basis, thenegative consequences that may arise if no interventions are undertaken. Congenital visual disordersdirectly affect the development of the visual system in children, disrupting the normal maturation of thevisual analyzer. In particular, if these pathologies are not identified or adequately treated during the earlyyears of life, profound and irreversible functional changes may occur in the visual system.Research indicates that congenital visual disorders can lead to the development of amblyopia(lazy eye), impaired binocular vision, decreased visual acuity, and strabismus. Furthermore, insufficientvisual stimulation may result in inadequate formation of neural connections in the visual areas of thecerebral cortex or irreversible neuronal changes. This not only limits visual function but also negativelyimpacts the child’s cognitive development, academic performance, and social adaptation.According to scientific sources, early diagnosis and treatment during the neuroplastic period ofthe visual system, id est, in the initial stages of childhood, are highly effective and can significantlyimprove visual functions. Therefore, widespread implementation of visual screening in children, earlyidentification of congenital visual disorders, and development of individualized treatment strategies foreach child are considered among the top priorities in pediatric ophthalmology
Keywords: ptosis; cataract; astigmatism